The Jews and the nation : revolution, emancipation, state formation, and the liberal paradigm in America and France - Jaher, Frederic Cople (Princeton University Press, 2002)
This book is the first systematic comparison of the civic integration of Jews in the United States and France--specifically, from the two countries' revolutions through the American republic and the Napoleonic era (1775-1815). Frederic Jaher develops a vehicle for a broader and uniquely rich analysis of French and American nation-building and political culture. He returns grand theory to historical scholarship by examining the Jewish encounter with state formation and Jewish acquisition of civic equality from the perspective of the "paradigm of liberal inclusiveness" as formulated by Alexis de